2003
DOI: 10.1002/jemt.10382
|View full text |Cite
|
Sign up to set email alerts
|

Imaging dislocations in ice

Abstract: Three techniques have been used to study dislocations in ice: etch pitting-replication, transmission electron microscopy, and X-ray topography (XT). It is shown that, because ice is a weak absorber of X-rays and can be produced with a low dislocation density, allowing relatively thick specimens to be studied, the most useful technique is XT. The observations that have been made with conventional XT are briefly outlined. However, the introduction of high-intensity synchrotron radiation, with its concomitant sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
(82 reference statements)
0
8
0
1
Order By: Relevance
“…However, most of the micro-inclusions were located in the grain interiors. Several EDX studies (Cullen and Baker, 2001; Barnes et al, 2002;Baker, 2003;Barnes, 2003;Iliescu and Baker, 2008) reported traces of sodium, chlorine and sulfur forming filaments at the sublimed ice surface. Some of the filaments grew at sites where grain boundaries and triple junctions intersected the surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the micro-inclusions were located in the grain interiors. Several EDX studies (Cullen and Baker, 2001; Barnes et al, 2002;Baker, 2003;Barnes, 2003;Iliescu and Baker, 2008) reported traces of sodium, chlorine and sulfur forming filaments at the sublimed ice surface. Some of the filaments grew at sites where grain boundaries and triple junctions intersected the surface.…”
Section: Introductionmentioning
confidence: 99%
“…8 Still, the nanometer-thickness range has eluded examination by microscopy, and important questions about multilayer ice growth remain, such as, e.g., why cubic ice often forms instead of hexagonal ice. The extreme sensitivity of ice to electron beam damage severely hampers the use of electron microscopy, 9,10 and x-ray topography with nanometer resolution has not been reported. 10 STM has not yet been applied to ice multilayer growth, perhaps because of the perception that the insulating character of ice prevents maintaining an electric current high enough to sustain the imaging process or that these currents will damage the film.…”
Section: Introductionmentioning
confidence: 99%
“…The extreme sensitivity of ice to electron beam damage severely hampers the use of electron microscopy, 9,10 and x-ray topography with nanometer resolution has not been reported. 10 STM has not yet been applied to ice multilayer growth, perhaps because of the perception that the insulating character of ice prevents maintaining an electric current high enough to sustain the imaging process or that these currents will damage the film. Here, we report how these constraints can be overcome and how STM can be used to gain insights into how ice grows on Pt͑111͒.…”
Section: Introductionmentioning
confidence: 99%
“…Востребованность рентгеновской топографии вызвала появление большого количества обзоров и монографий (например, [2][3][4][5][6][7][8][9][10][11][12][13][14][15] и [16,17], соответственно). Однако часть из этих обзоров -" возрастные" [2,3,5,7], часть посвящена конкретной узкой области применения рентгеновской топографии [4,6,8,[9][10][11][12]14].…”
Section: Introductionunclassified